1979
DOI: 10.1161/01.cir.60.5.1156
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of transthoracic electrical impedance in the diagnosis of pulmonary edema.

Abstract: To evaluate the clinical usefulness of measuring transthoracic electrical impedance in patients with pulmonary edema, we studied 27 normal subjects and 33 patients. In normal subjects, impedance increased when body position changed from supine to standing (p less than 0.01) and when lung volume increased from residual volume to total lung capacity (p less than 0.01). Impedance values vari7 omega) when measured hourly without removing the electrodes. In only five of 11 patients with clinically severe pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
5

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 13 publications
2
47
0
5
Order By: Relevance
“…The thermal dye double-indicator dilution technique remains one of the more accurate methods in intact humans and can determine small changes in EVLW, but it is highly invasive and would be difficult to perform in large numbers of subjects at altitude (42). Transthoracic electrical impedance measurement has been used at altitude (14,43), but the results have been disappointing and changes in lung volume with ventilation and the lack of spatial resolution further complicate the interpretation of results (11).…”
Section: Discussionmentioning
confidence: 99%
“…The thermal dye double-indicator dilution technique remains one of the more accurate methods in intact humans and can determine small changes in EVLW, but it is highly invasive and would be difficult to perform in large numbers of subjects at altitude (42). Transthoracic electrical impedance measurement has been used at altitude (14,43), but the results have been disappointing and changes in lung volume with ventilation and the lack of spatial resolution further complicate the interpretation of results (11).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies describe the assessment of lung edema by transthoracic bioimpedance measurements in pulmonary critical care, but the method has been found to be critical in lung tissue [17,18] . Measurements depend on the variations of air volume within the tissue, on a number of factors including body weight and position, lung volume and pleural effusions.…”
Section: Discussionmentioning
confidence: 99%
“…Later, clinical studies have employed the more conventional four-electrode configuration, 2 where the transthoracic impedance along the long axis of the thorax is measured. [3][4][5][6][7] This methodology was found to be better resistant to changes in tidal volume and chest movement errors. Still, these studies have shown inconsistent results, while not specifically measuring the lungs' impedance but rather that of the whole thoracic volume.…”
Section: Monitoring Lung Resistivity Changes In Congestive Heartmentioning
confidence: 98%